Effects of Digital Health Interventions on Pain, Maximum Mouth Opening, and Jaw Function in Individuals With Temporomandibular Disorders: A Systematic Review - Kailing Xu; Lanqi Li; Yinuo He; Fangyuan Jing; Jingxia Kong; Minmin Jiang (Journal of Oral Rehabilitation, 2026)
ABSTRACT Background Temporomandibular disorders (TMD) encompass a group of musculoskeletal and neuromuscular conditions involving the temporomandibular joint (TMJ), masticatory muscles, and associated structures. As an emerging self‐management approach, digital health interventions (DHIs) have demonstrated potential clinical value. Objective To investigate the effects of DHIs on pain, maximum mouth opening, and jaw function in individuals with TMD. Methods A literature search was performed in five electronic databases: PubMed, Web of Science, Embase, Cochrane Library, and MEDLINE, with the search date set to 18 January 2026. Inclusion criteria comprised randomised controlled trials (RCTs) evaluating DHIs for individuals with TMD that reported pain, jaw function, and maximum mouth opening (MMO) as primary outcomes. Risk of bias was assessed using the Risk of Bias 2 tool for all included studies. The certainty of evidence for each outcome was assessed using the GRADE approach. A narrative synthesis of the findings was subsequently performed. Results Six eligible RCTs were included, totaling 352 participants. The review assessed the effects of three types of DHIs, including mobile applications, internet‐based behavioural therapy (IBT), and telerehabilitation, for individuals with TMD. Under the descriptive umbrella of this narrative synthesis, mobile applications and telerehabilitation may be associated with improvements in pain, jaw function, and MMO. The certainty of evidence was rated as very low per GRADE criteria. No such benefits have yet been identified for IBT. Conclusion DHIs may be beneficial in reducing pain, increasing mouth opening, and improving jaw function in individuals with TMD. However, further high‐quality research is warranted to confirm these findings. Trial Registration PROSPERO Registration Number: CRD420261304970